2017
DOI: 10.1021/jacs.7b11754
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal Escape and Delivery of CRISPR/Cas9 Genome Editing Machinery Enabled by Nanoscale Zeolitic Imidazolate Framework

Abstract: CRISPR/Cas9 is a combined protein (Cas9) and an engineered single guide RNA (sgRNA) genome editing platform that offers revolutionary solutions to genetic diseases. It has, however, a double delivery problem owning to the large protein size and the highly charged RNA component. In this work, we report the first example of CRISPR/Cas9 encapsulated by nanoscale zeolitic imidazole frameworks (ZIFs) with a loading efficiency of 17% and enhanced endosomal escape promoted by the protonated imidazole moieties. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
342
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(364 citation statements)
references
References 27 publications
4
342
3
5
Order By: Relevance
“…The loading capacities of pEGFP‐C1@ZIF‐8 nanostructures and pEGFP‐C1@ZIF‐8‐PEI 25 kD nanostructures were determined by examining the concentration differences of pEGFP‐C1 in the supernatant before and after encapsulation via UV–vis absorption spectroscopy. After centrifugation to remove the nanostructures and extracting the pEGFP‐C1 from supernatant, the pEGFP‐C1 maximum loading content is calculated to be ≈2.5 wt% in pEGFP‐C1@ZIF‐8 nanostructures and ≈3.4 wt% in pEGFP‐C1@ZIF‐8‐PEI 25 kD nanostructures, respectively ( Figure a; Figure S9, Supporting Information), which is considered as the high loading capacities of MOF‐based vectors for high MW nucleic acids . Compared to pEGFP‐C1@ZIF‐8 nanostructures, the increased loading capacity of pEGFP‐C1@ZIF‐8‐PEI 25 kD nanostructures is attributed to the stronger electrostatic binding of the positive charged PEI 25 kD and the negatively charged pEGFP‐C1, as revealed by zeta potential analysis (Figure S10a, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The loading capacities of pEGFP‐C1@ZIF‐8 nanostructures and pEGFP‐C1@ZIF‐8‐PEI 25 kD nanostructures were determined by examining the concentration differences of pEGFP‐C1 in the supernatant before and after encapsulation via UV–vis absorption spectroscopy. After centrifugation to remove the nanostructures and extracting the pEGFP‐C1 from supernatant, the pEGFP‐C1 maximum loading content is calculated to be ≈2.5 wt% in pEGFP‐C1@ZIF‐8 nanostructures and ≈3.4 wt% in pEGFP‐C1@ZIF‐8‐PEI 25 kD nanostructures, respectively ( Figure a; Figure S9, Supporting Information), which is considered as the high loading capacities of MOF‐based vectors for high MW nucleic acids . Compared to pEGFP‐C1@ZIF‐8 nanostructures, the increased loading capacity of pEGFP‐C1@ZIF‐8‐PEI 25 kD nanostructures is attributed to the stronger electrostatic binding of the positive charged PEI 25 kD and the negatively charged pEGFP‐C1, as revealed by zeta potential analysis (Figure S10a, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Encapsulation of Cas9/sgRNA by ZIF‐8 for endosomal escape and gene editing. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Mof Proteinsmentioning
confidence: 77%
“…A recent approach to load a combination of protein (CRISPR/Cas9, associated protein 9) and engineered RNA (sgRNA) to form a single guide genome editing platform into ZIF‐8 framework has helped to resolve the issue associated with the combined delivery of large molecules. It is interesting to find out the possible reasons for the efficiency of endosomal escape prerequisite to build a therapeutic solution ( Figure ) . The authors found a facile release mechanism of CC‐ZIFs by the complete dissolution of the protective ZIF‐8 shell.…”
Section: Mof Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[195,196] Yang et al found that the ZIF-90 could be disintegrated by high concentration of ATP (10 × 10 −3 m) and released the protein inside cells due to the competitive coordination between Zn 2+ and ATP that disassembles ZIF-90. The ZIF-90 or ZIF-8/Cas9 RNP nanocarriers could be fabricated by self-assembling with Zn 2+ , proteins and imidazole-2-carboxaldehyde (2-ICA) or 2-methylimidazole.…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%